ROBERT ENTMAN FRAMING ANALYSIS OF SARACEN HOAK ISSUE NEWS IN REPUBLIKA.CO.ID AND KOMPAS.COM - M. Syamsul Arifin; Diki Iskandar; Teti Sobari (JLER (Journal of Language Education Research), 2020)
Online media is now more popular than conventional media because of the speed, ease of access and the information provided is always new. In reporting, it is always influenced by ideology, power and the interests of media owners. This study aims to find out how a media frame and construct the reality of news about the Saracen issue in republika.co.id and kompas.com. This study uses Robert’s framing which focuses on how to define a problem, what / who causes the problem, what moral decision is in the news and what the settlement is offered by journalists. The results of this study indicate that in constructing and framing the Saracen issue both in republika.co.id and kompas.com have a different impression. Where republika.co.id tends to be careful that the Saracen issue will divide the nation while kompas.com asks President Jokowi to arrest and punish the perpetrators of the Saracen issue for dividing the nation. Keywords: Online Media, Robert Entman Framing Analysis, Saracen